2021
DOI: 10.1371/journal.pone.0253662
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the 4Ps Model of Transitioning to Distance Learning: A convergent mixed methods study conducted during the COVID-19 pandemic

Abstract: Significant concern has been raised regarding the effect of COVID-19 on medical education. This study aimed to shed light on the distance learning experiences of medical students and their instructors at the Mohammed Bin Rashid University of Medicine and Health Sciences (MBRU) in Dubai, United Arab Emirates. A convergent mixed methods approach was utilized. Qualitative and quantitative data was collected using a survey of closed-ended followed by open-ended questions. The percentage of the total average of sat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
0
18
0
4
Order By: Relevance
“…In terms of the stakeholders’ perception of the experience, both groups appeared quite satisfied. The total average of satisfaction among stakeholders was 76.4% [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the stakeholders’ perception of the experience, both groups appeared quite satisfied. The total average of satisfaction among stakeholders was 76.4% [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The final component assessed the perception of both groups of stakeholders of the transition experience (as a whole). In the context of our study, the tool proved to be internally consistent and externally valid [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…MBRU is one of 8 medical colleges in the UAE and one of two in Dubai. MBRU was established in 2016, and currently offers a 6-year Bachelor of Medicine, Bachelor of Surgery (MBBS) program [ 10 , 30 , 31 ] as well as postgraduate degrees in dentistry [ 11 , 32 , 33 ], nursing, and biomedical sciences. The first 3 years of the respective MBBS program are preclinical and the remaining years are spent in the clinical setting.…”
Section: Methodsmentioning
confidence: 99%
“…The study's ethical approval was granted by the Mohammed Bin Rashid University of Medicine and Health Sciences (MBRU), Institutional Review Board (Reference # MBRU-IRB-2020-028). A multi-phased convergent mixed methods study design (38)(39)(40)(41) was adopted, as demonstrated in Figure 1, to systematically, from a macro perspective, understand the patients' perceptions regarding the quality of their experience with telehealth medicine.…”
Section: Methodsmentioning
confidence: 99%